Pseudohypoparathyroidism with Hashimoto's thyroiditis and Turner syndrome: a case report. (10th June 2014) - Zeng, Wen-Heng; Xu, Jiao-Jun; Jia, Min-Yue; Ren, Yue-Zhong
Abstract: Objective : To report the case of an individual with PHP, Turner syndrome and Hashimoto's thyroiditis. Case : A 16-year-old girl was referred to our hospital with chief complaint of short stature. She presented with round chubby facies, short neck, obesity and short stature. Radiography indicated short metatarsals and metacarpals, which mainly affected the second, third and fourth digits. Biochemistry revealed hyperphosphatemia, increased serum concentrations of parathyroid hormone and thyroid stimulating hormone, elevated levels of follicular-stimulating hormone and prolactin, and increased thyroid peroxidase antibody and thyroglobulin antibody. Radiographic examination revealed delayed bone age and pelvic ultrasonography demonstrated an immature uterus. Karyotype analysis showed 46, X, i(Xq10), while molecular analysis revealed a same sense mutation in exon 5 of GNAS (ATC → ATT, Ile).The specific diagnosis was made of Turner syndrome in the presence of Hashimoto's thyroiditis and PHP. She was treated with calcium supplementation, calcitriol and thyroxine. Conclusions : This is the first case report to describe a combination of Turner syndrome with these other clinical entities, and their co-existence should be considered and further investigated. Chinese abstract: 目的：本文旨在对一例同时患有PHP、特纳综合征以及桥本氏甲状腺炎的病例进行报道。 病例：我院接诊了一名16岁的女孩，主诉为身材矮小。其外貌特征为圆脸、颈短、肥胖以及身材矮小。放射学检查指出其跖骨及掌骨短小，这主要影响到她的第二节、第三节及第四节手指。生化检查提示伴有高磷酸血症，血清甲状旁腺激素、促甲状腺激素水平升高，卵泡刺激素及泌乳素水平也较高，同时还有甲状腺过氧化物酶抗体水平以及甲状腺球蛋白抗体水平升高。放射学检查提示其骨龄延迟，盆腔超声检查提示子宫发育不成熟。染色体核型分析结果为46, X, i(Xq10)，进一步的分子学检查提示GNAS外显子5发生突变(ATC → ATT, Ile)。特异性诊断为特纳综合征伴有桥本氏甲状腺炎以及PHP。治疗方案为补充钙剂、骨化三醇以及甲状腺素。 结论：这是第一例患有特纳综合征同时还有其它临床疾病的病例，这种共同存在的特性需要进行更进一步的探讨。